Agricultural Products in the Levant (4-6 AH/ 10-12 CE) - Ako Burhan Muhamad; Bahar Abbas Jubraeil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research is an endeavor to unveil and examine the economic aspects of the agricultural ways of life that were prevalent in the Levant during 4-6 AH/10-12 CE. Domestically, the region had outstanding economic patterns that influenced not only the territories under the jurisdiction of the Islamic Empire, but other regions around the globe as well. Throughout the reign of the Islamic Empire, the Levant, due to its fertile soil, had been described as a paradise. Agriculture is one of the fundamental principles in economics that can potentially aspire to prosperity and improvements in the sociopolitical spheres of various human communities. This study encompasses all the common cultivated products in the Levant at the stated period, including crops, vegetables, and heat and drought-tolerant, fruit-bearing trees and plants, in addition to prunus and citrus shrubs. This research demonstrates that the Levant has a fertile soil to grow various types of agricultural goods. Furthermore, it shows that all the spots of the region are not invariably feasible sowing the same seeds and that, in certain areas, a selection of trees and shrubs bear numerous types of agricultural goods. For example, Damascus has more than 50 types of grapes. And, due to the abundance of agrarian and farming lands, villages, valleys, and mountains surrounding Damascus are often named after fruits or vegetables. The literature underpinning this research is largely reflected in the ancients and contemporary works and studies of geographists, historians, and anthropologists.